Challenges in Managing Infraclavicular Node Metastasis in Breast Cancer with Aggressive Locoregional Surgery: A Case Report - Dr. Swathika Rajendran , Dr. Murali Krishnan Vummiti (South Eastern European Journal of Public Health, 2025)
The treatment of breast cancer with axillary lymph node metastasis can sometimes be difficult to manage. This case report presents an unusual occurrence of lymph node metastasis in a 28-year-old woman diagnosed with infiltrating ductal carcinoma of the breast, accompanied by axillary lymph node involvement. The patient underwent neoadjuvant chemotherapy, followed by a mastectomy and level 3 axillary lymph node dissection. The postoperative histopathological examination revealed a complete pathological response in the breast tissue; however, four axillary lymph nodes were found to have metastatic disease. Three of them were reported to have macro metastases and one node showed fibrosis with evidence of treatment response. As an unusual development, further postoperative staging investigations revealed an infraclavicular lymph node metastasis that was absent in preoperative imaging. Given the isolated nature of the infraclavicular metastasis, a locoregional excision was carried out to mitigate the risk of further distant metastases and enhance local disease control. This rare presentation highlights the difficulties involved in managing breast cancer with metastatic axillary lymph node and the possibility of unexpected disease progression despite initial treatment response.